Caffeine Drink and Energy Gel Increase Aerobic Endurance - Satria, Mochamad Rafli; Roy Januardi Irawan; Ananda Perwira Bakti; Anindya Mar'atus Sholikhah (Universitas PGRI Palembang, 2024)
Human physical abilities are divided into anaerobic and aerobic abilities, where aerobic endurance (cardiovascular fitness) involves the process of oxygen uptake, transport and utilisation. Coffee consumption before exercise can improve performance and prevent fatigue, especially if caffeine is consumed one hour before exercise, which can improve running performance. The aim of this study was to examine the effectiveness of caffeinated drinks and energy gels before high-intensity exercise over a long period of time. This study used a pretest-posttest method with participants of 30 students from extracurricular futsal at MAN Lumajang, divided into two groups: E1 (caffeinated drink) and E2 (energy gel), 15 students each. Measurements used the Balke test and data were analysed using the Mann Whitney test in SPSS. The results of hypothesis analysis using the Mann-Whitney test showed a significant difference between variables E1 (caffeinated drink) and E2 (energy gel) with a significance value of p = 0.011, indicating a significant difference between the two groups. The conclusion of this study is that caffeinated drinks and energy gel provide different impacts in improving aerobic endurance performance.